The Splendid Allure of Europium at the Inaugural Montréal/Nouvelles Musiques - Steenhuisen, Paul (Circuit, 2004)
Composer Paul Steenhuisen shares his own views on the Montréal/Nouvelles Musiques Festival by situating it within the context of other Canadian festivals and by discussing its main characteristics. The author also discusses the festival's artistic principles and its thematic orientation. On considering the compartmentalization of the public, he suggests that an artistic approach based on a unifying musical or philosophical idea would be an advantageous replacement to the "star composer" system.